2012
DOI: 10.1016/j.gie.2011.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Prague C & M criteria for the endoscopic grading of Barrett's esophagus by gastroenterology trainees: a multicenter study

Abstract: Background The Prague C & M Criteria, developed for the endoscopic grading of Barrett's esophagus (BE), (C=circumferential length, M=maximal length) were previously validated among a panel of 30 expert endoscopists with a special interest in BE. Its performance among gastroenterology (GI) trainees is unknown. Objective To test inter-observer agreement among GI trainees for the Prague C & M criteria, identification of the gastroesophageal junction (GEJ) and the diaphragmatic hiatus. Design A prospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…Regarding BE length, as most of the results were obtained prior to the establishment of the Prague criteria (C, circumferential extent, and M, maximum extent) (22,23), BE was measured in centimeters, counting from the esophageal gastric junction (EGJ) to the proximal section of the squamocolumnar junction hence distinguishing short BE (< 3 cm) from long BE (> 3 cm). Once these data were obtained for each group, a multivariate comparison analysis was carried out, with the purpose of determining possible risk factors with an influence on the histopathological behavior of BE and EAC.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding BE length, as most of the results were obtained prior to the establishment of the Prague criteria (C, circumferential extent, and M, maximum extent) (22,23), BE was measured in centimeters, counting from the esophageal gastric junction (EGJ) to the proximal section of the squamocolumnar junction hence distinguishing short BE (< 3 cm) from long BE (> 3 cm). Once these data were obtained for each group, a multivariate comparison analysis was carried out, with the purpose of determining possible risk factors with an influence on the histopathological behavior of BE and EAC.…”
Section: Methodsmentioning
confidence: 99%
“…The score has been validated among experts 18 and in two additional studies among trainees and community-based endoscopists, strengthening the value of the Prague classification for the accurate description of Barrett's esophagus and the length of the hiatal hernia. 27,28 The ESGE guideline on the diagnosis and management of nonvariceal UGI bleeding has strongly recommended the uniform use of the Forrest classification, as used in several studies assessing the risk for peptic ulcer bleeding and rebleeding. 29,30 Therefore it is clinically important that this classification is used in the endoscopy report in order to ascertain the correct clinical management after endoscopy for UGI bleeds.…”
Section: -13mentioning
confidence: 99%
“…The clinical diagnosis is based on the endoscopic recognition of red/pink gastric-like mucosa lining the tubular esophagus above the EGJ, which is defined as the most proximal margins of the gastric folds in the West (the Prague C & M criteria) [10][11][12] and as the lower end of the palisade vessels of the lower esophagus in Japan (the Japanese criteria) [13][14][15]. In patients with severe atrophic gastritis, particularly Asian and Japanese individuals with Helicobacter pylori, the infection-which spreads through the cardia from the antrum-atrophic gastritis-makes it difficult for the oral end of the gastric folds to be used as a marker of the EGJ.…”
Section: Argument Regarding Landmark Of Esophagogastric Junction In Tmentioning
confidence: 99%
“…The overall reliability coefficients for the endoscopic recognition of BE C1 cm was 0.72, whereas for the endoscopic recognition of BE \1 cm of columnarlined epithelium (CLE), the coefficient was only 0.22 [12]. One possible reason for the difficulty may be the use of a different definition of the EGJ as discussed above [10][11][12][13][14][15]. In studies based in the USA, only cases in which SIM was histologically confirmed in CLE were defined as BE, of any length.…”
Section: Argument Regarding Landmark Of Esophagogastric Junction In Tmentioning
confidence: 99%